2004
DOI: 10.1016/j.tetlet.2004.04.090
|View full text |Cite
|
Sign up to set email alerts
|

The rational design of modified Cinchona alkaloid catalysts. Application to a new asymmetric synthesis of chiral chromanes

Abstract: Abstract-A new asymmetric synthesis of 2-substituted chiral chromanes has been achieved. The key step is the intramolecular conjugate addition of a phenolic nucleophile on a a,b-unsaturated ester catalyzed by Cinchona alkaloids. The high ee's obtained with cinchonine and its derivatives have been rationalized by ab initio quantum chemistry calculations of transition state structures. Ó 2004 Elsevier Ltd. All rights reserved.Functionalized chromanes possess potentially useful biological properties.1 In the scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…141 Functionalised chromanes possess potentially useful biological properties. 142 High enantioselectivities were observed with cinchonine and its derivatives 246aed.…”
Section: Intramolecular Oxa-michael Additionmentioning
confidence: 99%
“…141 Functionalised chromanes possess potentially useful biological properties. 142 High enantioselectivities were observed with cinchonine and its derivatives 246aed.…”
Section: Intramolecular Oxa-michael Additionmentioning
confidence: 99%
“…31a,32 Merschaert et al have also used cinchona alkaloid derivatives as catalysts in the first asymmetric 6-exo-trig oxa-Michael addition reaction of a phenolic nucleophile on an a,b-unsaturated ester for the synthesis of 2-substituted chromanes. 33 Among the readily available cinchona alkaloids, the best results were obtained using cinchonine (10 mol %) as catalyst (27 in Fig. 3).…”
Section: 4-additions Of Oxygenated Nucleophiles Catalyzed By Cinchomentioning
confidence: 99%
“…After a broad screening of these modified catalysts, 28 was found to give the highest enantioselectivities for both Z (80% ee) and E (52% ee) isomers, although with a slight decrease in conversion. 33 The highly enantioselective cyclization of 2 0 -hydroxychalcones to flavanones catalyzed by the enzyme chalcone isomerise, is a well-known step in the biosynthesis of flavonoids. It cannot, however, be reproduced enantioselectively so far using asymmetric organocatalysis.…”
Section: 4-additions Of Oxygenated Nucleophiles Catalyzed By Cinchomentioning
confidence: 99%
“…9 Various catalysts have been reported for intermolecular oxa-Michael additions, such as pro-azaphosphatranes of ionic liquid as solvent for toluenesulfonic acid-catalyzed oxa-Michael addition has also been reported. 22 For intramolecular oxa-Michael addition, cinchona alkaloids, 23 thiourea derivatives, 24 quinine, 25 guanidine, 26 30,31 have been utilized as the catalysts. It was reported that the intramolecular oxa-Michael addition of (E)-1-aryl-4-hydroxy-4-methylpent-1-en-3-ones in the presence of TsOH should be carried out by refluxing in dichloroethane for 24 h, while the products were hard to purify due to the impurities.…”
Section: Introductionmentioning
confidence: 99%